Case Report: Identification of a novel hemizygous CFAP47 variant in a primary ciliary dyskinesia patient with dual ciliary and flagellar defects - He, Miao; Zhou, Wangji; Li, Yixuan; Chen, Qiaoling; Liu, Yaping; Tian, Xinlun; Zhang, Xue (Frontiers in Medicine, 2025)
BackgroundPrimary ciliary dyskinesia (PCD) is a genetically heterogeneous ciliopathy caused by structural and functional abnormalities of motile cilia. Although over 50 PCD-associated genes have been reported, the genetic spectrum remains incomplete. CFAP47, a gene linked to multiple morphological abnormalities of the flagella, has recently been implicated in PCD; however, further case studies are needed to strengthen this conclusion.MethodsWe investigated a male patient with suspected PCD who exhibited “9 + 2” ultrastructural abnormalities in both bronchial cilia and sperm flagella. Whole exome sequencing was performed to screen for pathogenic variants. The candidate variant was analyzed through bioinformatics tools, and CFAP47 expression levels were quantified via qPCR in both patient-derived sperm and an in vitro expression plasmid model.ResultsWhole exome sequencing identified a hemizygous missense variant, CFAP47 (NM_001304548.2): c.3599T > A (p.Phe1200Tyr) in the patient. The pathogenicity of this variant was assessed through multiple in silico tools, with divergent predictions. Experimental validation revealed significantly decreased CFAP47 mRNA levels in the patient’s sperm and the HEK293 cells transfected with mutant plasmid compared to controls, suggesting impaired transcript stability.ConclusionOur study proposes a novel CFAP47 variant as a likely contributor to PCD, given its impact on mRNA expression. These findings strengthen the association between CFAP47 and PCD pathogenesis and expand the mutation spectrum of this emerging disease gene.